Impact of food matrix and processing on the in vitro bioaccessibility of vitamin C, phenolic compounds, and hydrophilic antioxidant activity from fruit juice-based beverages. (April 2015) - Rodríguez-Roque, María Janeth; de Ancos, Begoña; Sánchez-Moreno, Concepción; Cano, M. Pilar; Elez-Martínez, Pedro; Martín-Belloso, Olga
Highlights: Food matrix and processing modulated the bioaccessibility of hydrophilic compounds. Soymilk-fruit juice beverages showed the greatest bioaccessibility of vitamin C. Water-fruit juice beverages favoured the bioaccessibility of phenolic compounds. Food processing increased the bioaccessibility of some phenolic compounds. HIPEF and HPP allow obtaining beverages with improved nutritional quality. Abstract: The effect of food matrix (water-, milk-, or soymilk-fruit juice beverages) and processing [high-intensity pulsed electric fields (HIPEF); high-pressure processing (HPP); and thermal treatment (TT)] on the in vitro bioaccessibility of vitamin C and phenolic compounds, as well as on the hydrophilic antioxidant activity (HAA) of fruit juice-based beverages was analysed. HIPEF and HPP improved or did not change the bioaccessibility of vitamin C and certain phenolic compounds in comparison with untreated beverages. In contrast, TT diminished the bioaccessibility of most of these compounds. The greatest vitamin C bioaccessibility was obtained in soymilk-fruit juice beverages (SB), whereas water-fruit juice beverages (WB) favoured the bioaccessibility of phenolic compounds and HAA. Milk-fruit juice beverages (MB) reduced the bioaccessibility of these hydrophilic constituents. Results showed that both food matrix and processing modulated the bioaccessibility of vitamin C and phenolic compounds of fruit juice-based beverages. Furthermore, HPP and HIPEF allow obtaining beverages with improved nutritional and functional quality.